Case Report: Latent Syphilis in the Second Trimester of Pregnancy - Vanda Tri Andini; Dian Amelia Abdi; Abdul Azis (The International Journal of Medical Science and Health Research, 2025)
Syphilis is a sexually transmitted infection caused by exposure to the bacterium Treponema pallidum. Syphilis is predominantly transmitted through sexual intercourse, from mother to fetus, and through blood transfusion processes. In pregnant women with syphilis, the Treponema pallidum bacterium is transmitted from the mother to the fetus through the placental capillary blood vessels. This case report discusses a 27-year-old married female patient who presented at the Cendrawasih Public Health Center (PKM) for Antenatal Care. During the examination, the patient did not report any complaints of headache, nausea, vomiting, or back pain. A history of red spots on the palms, soles, and mouth was denied. The patient also denied having any odorous vaginal discharge, or itching or burning sensations on her body. A history of sores or lumps around the genital area was denied. There were no indications of complaints related to significant weight loss, diarrhea, persistent cough, or fever. A history of joint pain or enlarged glands was also denied. Syphilis is caused by the Treponema pallidum bacterium, which has chronic and systemic characteristics. Syphilis can be generally classified into two groups: congenital and acquired. Congenital syphilis typically presents with symptoms such as hepatosplenomegaly, neurosyphilis, fever, skin lesions, comprehensive lymphadenopathy, and pneumonitis. In contrast, acquired syphilis is usually characterized by a single ulcer (chancre), a body rash, fever, and malaise. A definitive diagnosis is made using a darkfield microscope, PCR, or a direct fluorescent antibody test.